Microbiological and Biochemical Contamination Analysis of Refilled Drinking-water in Abeli, Kendari, Southeast Sulawesi - Juminten Saimin; Hartati Hartati; Yenti Purnamasari; Sufiah Asri Mulyawati; Tien Tien; Pranita Ayitrina (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: The access to safe drinkingwater is increasingly difficult, especially in water catchment or coastal areas. Due to the difficulty, people in coastal areas tend to consume ready-to-use refilled drinking-water. However, the sanitation facilities on most drinking-water refill depots do not meet the requirements, hence really prone to microbial contamination. We conducted this study to determine the types of bacteria causing the contamination of refilled drinking-water from refill depots in Abeli, a coastal area in Kendari.METHODS: Samples were collected from all 6 drinkingwater refill depots in Abeli. Three-series fermentation tubes were used for the microbiological test, including the presumptive, confirmative and completed tests. The biochemical test was performed with indole test, methyl red test, Voges-Proskauer test, and citrate utilization test (IMViC) methods and the triple sugar iron agar (TSIA) test.RESULTS: Among 6 refilled drinking-water samples, we found the growth of coliform bacterial colonies in 3 samples, exhibiting various characteristics. Based on the characteristics, both microbiological and biochemical, the identified bacteria were Proteus sp., Escherichia coli and Klebsiella oxytoca.CONCLUSION: Bacteria that contaminated refilled drinking-water in Abeli were Proteus sp., E. coli and K. oxytoca. Continuous supervision is required to ensure the quality of water from drinking-water refill depots.KEYWORDS: bacteria, Proteus sp., Escherichia coli, Klebsiella oxytoca, coastal areas, refilled drinking water